Evolution of competition in energy alternative pathway and the influence of energy policy on economic growth. (August 2015) - Yang, Honglin; Wang, Lin; Tian, Lixin
Abstract: This work is devoted to the evolution of the competition of energy alternative pathway in China, and the influence of energy policy on economic growth by using a dynamical system method. Firstly, the relation between energy and economic growth is taken into account, and a dynamic evolution model is established. It is observed that Hopf bifurcation and chaotic behavior occurs with the varying investment in renewable energy production. Secondly, when there is no policy intervention in energy market, the evolution of competition in energy alternative pathway is also investigated. Thirdly, the system parameters are also identified by using an artificial neural network method on the basis of certain empirical statistical data in China, and the dynamics of the parameters-identified system are studied. Finally, the influences of energy policy on economic growth are empirically analyzed, and some policy recommendations are given based on the results of empirical analysis. Highlights: Modeling the energy economy system via the method of dynamic system. Attaining the chaotic attractor of the energy production and economic system. Discovering the Hopf bifurcation when the investment changes. Proposing the alternative pathway of free competition in energy production. Determining the turning points of parameters related to policy regulation.